Evolutionary conservation of an atypical glucocorticoid‐responsive element in the human tyrosine hydroxylase gene. (28th May 2013) - Sheela Rani, C. S.; Soto‐Pina, Alexandra; Iacovitti, Lorraine; Strong, Randy
Abstract The human tyrosine hydroxylase (hTH) gene has a 42 bp evolutionarily conserved region designated (CR) II at −7.24 kb, which bears 93% homology to the region we earlier identified as containing the glucocorticoid response element, a 7 bp activator protein‐1 (AP‐1)‐like motif in the rat TH gene. We cloned this hTH‐CRII region upstream of minimal basal hTH promoter in luciferase (Luc) reporter vector, and tested glucocorticoid responsiveness in human cell lines. Dexamethasone (Dex) stimulated Luc activity of hTH‐CRII in HeLa cells, while mifepristone, a glucocorticoid receptor (GR) antagonist, prevented Dex stimulation. Deletion of the 7 bp 5′‐TGACTAA at −7243 bp completely abolished the Dex‐stimulated Luc activity of hTH‐CRII construct. The AP‐1 agonist, tetradeconoyl‐12, 13‐phorbol acetate (TPA), also stimulated hTH promoter activity, and Dex and TPA together further accentuated this response. Chromatin immunoprecipitation assays revealed the presence of both GR and AP‐1 proteins, especially Jun family members, at this hTH promoter site. Dex did not stimulate hTH promoter activity in a catecholaminergic cell line, which had low endogenous GR levels, but did activate the response when GR was expressed exogenously. Thus, our studies have clearly identified a glucocorticoid‐responsive element in a 7 bp AP‐1‐like motif in the promoter region at −7.24 kb of the human TH gene.